Penguatan Nilai-Nilai Anti Korupsi dalam Pembelajaran Pendidikan Pancasila dan Kewarganegaraan pada Siswa Kelas VII di SMP Negeri 1 Sidoarjo - Nanda Aprilia Ningrum; Rahmanu Wijaya (Medan Resource Center, 2023)
This study aims to describe the strengthening of anti-corruption values in Civics learning at SMP Negeri 1 Sidoarjo. The type of research used in this study is descriptive-qualitative. The data collection techniques are interviews, observation, and documentation. The research results of strengthening anti-corruption values in Pancasila and Citizenship Education learning for seventh grade students at SMP Negeri 1 Sidoarjo show that there are four ways carried out by teachers, namely by providing knowledge related to anti-corruption values, providing moral direction in form of advice and stories of real events that contain anti-corruption values, providing role models to students related to anti-corruption values, and providing rewards and sanctions to students. Furthermore, the evaluation carried out by Civics teachers in strengthening anti-corruption values is conducted through an attitude assessment. In strengthening anti-corruption values, teachers experience obstacles, namely the lack of awareness among students. The solution is to give advice to students continuously.